Influence of micronutrients on dry matter yield and interaction with other nutrients in annual crops - Fageria, Nand Kumar (Pesquisa Agropecuaria Brasileira, 2002)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} p.MsoBodyText, li.MsoBodyText, div.MsoBodyText {margin:0cm; margin-bottom:.0001pt; text-align:center; mso-pagination:widow-orphan; font-size:13.5pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; font-weight:bold;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The objective of this work was to determine the influence of Zn, Mn and Cu on shoot dry matter yield and uptake of macro and micronutrients in upland rice, common bean and corn. Six greenhouse experiments were conducted using a Dark Red Latosol (Typic Haplusthox). Treatments consisted of application of Zn at 0, 5, 10, 20, 40, 80 and 120 mg kg-1, of Mn at 0, 10, 20, 40, 80, 160, 320 and 640 mg kg-1 and of Cu application at 0, 2, 4, 8, 32, 64 and 96 mg kg-1. Zinc increased yield of rice, Mn increased yields of corn and bean and Cu improved yields of rice and bean. Uptake of N, Ca, and Cu in rice was decreased by zinc treatment. In common bean, uptake of N, Mg, and Cu was increased by zinc application, whereas, uptake of P was decreased. Manganese increased uptake of Mg, Zn and Fe and decreased uptake of Ca, in corn. Uptake of K, Zn and Mn was increased and uptake of P and Cu was decreased by Mn application, in bean. Copper had positive and negative interactions in the uptake of macro and micronutrients, depending on crop species and nutrients involved.